Formation of Sports Culture As the Priority Problem of Sports Work in a University - S. U. Barinov (Vestnik MGIMO-Universiteta, 2012)
It's clearly shown in the article, that sport education of students is the most important aspect of all sport activities. Taking into account the rule of humane pedagogics that mental development is the goal and the main object of educational activity, the formation of sport culture should be considered at the very first place. In the article, the author outlines patterns of sport culture and its variations.